Detection of circumstellar material in a normal type Ia supernova. - Patat, F; Chandra, P; Chevalier, R; Justham, S; Podsiadlowski, P; Wolf, C; Gal-Yam, A; Pasquini, L; Crawford, I; Mazzali, P; Pauldrach, A; Nomoto, K; et al. (2007)
Type Ia supernovae are important cosmological distance indicators. Each of these bright supernovae supposedly results from the thermonuclear explosion of a white dwarf star that, after accreting material from a companion star, exceeds some mass limit, but the true nature of the progenitor star system remains controversial. Here we report the spectroscopic detection of circumstellar material in a normal type Ia supernova explosion. The expansion velocities, densities, and dimensions of the circumstellar envelope indicate that this material was ejected from the progenitor system. In particular, the relatively low expansion velocities suggest that the white dwarf was accreting material from a companion star that was in the red-giant phase at the time of the explosion.